Numerical simulation of thin layer coffee drying by control volumes (2010)
The thin layer drying model proposed by Sokhansanj and Bruce (1987) was implemented to model the drying process of parchment coffee beans. A computational model based on a control volume approach was developed to simulate the drying process of parchment coffee. A one dimensional transient analysis was implemented in the radial direction applied to a spherical coffee bean of equivalent radius. The results found that, even though the numerical value for the mass transfer coefficient is a small number (about of 10⁷ m/sec), moisture content predictions were sensitive to this value. The predicted drying curve compared favorably with published results.